2013
DOI: 10.1002/cbic.201200522
|View full text |Cite
|
Sign up to set email alerts
|

The Marine Polyketide Myriaporone 3/4 Stalls Translation by Targeting the Elongation Phase

Abstract: Myriaporone 3/4, a cytotoxic polyketide, has been reported as an inhibitor of eukaryotic protein synthesis. However, the mechanism by which it inhibits translation was unknown. Here we show that myriaporone 3/4 stalls protein synthesis in the elongation phase by inducing phosphorylation of eukaryotic elongation factor 2. The phosphorylation results from direct binding of myriaporone 3/4 to eukaryotic elongation factor 2 kinase. Our study also shows that myriaporone 3/4 in the nanomolar range inhibits in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
0
5
0
1
Order By: Relevance
“…Eine Induktion einer eEF2‐Phosphorylierung wurde auch schon mit den Myriaporonen 3 und 4 gefunden. Über DARTS‐Experimente konnte gezeigt werden, dass dies offensichtlich über eine direkte Bindung von Myriaporon an die eEF2‐Kinase geschieht 13. Mit 7 erhielten wir aber keine Hinweise auf eine direkte Bindung.…”
Section: Methodsunclassified
“…Eine Induktion einer eEF2‐Phosphorylierung wurde auch schon mit den Myriaporonen 3 und 4 gefunden. Über DARTS‐Experimente konnte gezeigt werden, dass dies offensichtlich über eine direkte Bindung von Myriaporon an die eEF2‐Kinase geschieht 13. Mit 7 erhielten wir aber keine Hinweise auf eine direkte Bindung.…”
Section: Methodsunclassified
“…Two polyketides of another group, macrolides tedanolide and 13 deoxytedanolide, also block translocation by binding to the same location in the E site as pederins [61,89]. Surprisingly, structurally similar myriaporones [90] sup press elongation by phosphorylation of the elongation factor eEF2, rather than by direct binding to the ribo some [91,92].…”
Section: Inhibitors Of Eukaryotic Ribosomementioning
confidence: 99%
“…Through drug affinity responsive target stability (DARTS) experiments,itcould be shown that this was due to direct binding of myriaporone to eEF2 kinase. [13] With 7,w e did not observe any indication of direct binding. Thefact that 7 inhibits translation at two separate sites of the translation machinery explain its high efficacy.Desepoxyisotedanolide (6), which was much less effective in blocking the translation process,o bviously inhibits the elongation phase only,w hich makes it less efficacious than 7 (Figure 9).…”
Section: Methodsmentioning
confidence: 83%
“…Through drug affinity responsive target stability (DARTS) experiments,itcould be shown that this was due to direct binding of myriaporone to eEF2 kinase. [13] With 7,w e did not observe any indication of direct binding.…”
Section: Angewandte Chemiementioning
confidence: 78%